PREDICTING THE FLEXURAL RESPONSE OF A REINFORCED CONCRETE BEAM USING THE FRACTURE-PLASTIC MODEL - Asdam Tambusay; Priyo Suprobo (Journal of Civil Engineering, 2019)
This paper describes an attempt to predict the flexural response of a reinforced concrete (RC) beam using nonlinearfinite element analysis. To facilitate direct comparison, the beam was tested experimentally under four-point bending with theload increased monotonically. The load-deflection response, crack pattern and failure mode were observed in the experiment.Analysis incorporating the application of ATENA 3D was performed using the fracture-plastic model which is based on theclassical orthotropic smeared crack formulation and crack band model. The applicability of this model was demonstratedthrough detailed simulation of RC beam with identical geometry, reinforcement arrangement, and material properties. Fromthis study, it is found that the overall predicted responses are in very good agreement to those obtained from the experiment.It is also found that the feature in ATENA enables the presentation of reasonably maximum principal strains of concrete andrebar elements which can, therefore, be associated with the predicted crack bands.